2003
DOI: 10.4067/s0716-97602003000200015
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activities of Iodoacetate and Dimethylsulphoxide Against Solid Ehrlich Carcinoma Growth in Mice

Abstract: Treatment of tumor-bearing mice with LD 12.5 values of iodoacetate; IAA (1.84 mg/100g b.w.) and/or dimethylsulphoxide; DMSO (350 mg/ 100g b.w.) significantly increased the cumulative mean survival time and percentage of survivors and reduced the mean tumor weight, compared to tumor-bearing controls, however, a more pronounced effect is recorded in the combined treatment. Also, an increase in the life span (ILS%) and tumor growth inhibition ratio (T/C%) are reported and amounted to 145.78 and 43.80%, 195.54 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…These results were in the same line with Fahim et al (2003). This was attributed to the effects of Ehrlich tumor on the body with alteration of metabolism, decreased immunity, severe anemia and induction of cachexia (Kumar et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…These results were in the same line with Fahim et al (2003). This was attributed to the effects of Ehrlich tumor on the body with alteration of metabolism, decreased immunity, severe anemia and induction of cachexia (Kumar et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…We show here that inhibition of GAPDH efficiently reduces the growth of colon cancer cells in vitro. Interestingly, although the GAPDH inhibitor Na iodoacetate has been shown to reduce the growth of Ehrlich ascites carcinoma (EAC) cells and xenografts of colon cancer cells at doses similar or lower than the one used in vivo in this study (35,36), no significant effects were observed here on the growth of subcutaneous xenografts of four different colon cancer cell lines. However, no toxicity was observed at the doses used, and based on the in vitro effects observed, it remains possible that Na iodoacetate treatment at higher doses and/or in other tumor cell lines, may interfere with tumor growth.…”
Section: Discussionmentioning
confidence: 61%
“…If inhibition in energy production reported above by others was responsible for observing any inhibition of the induction of genetic events, it would have inhibited all the end-points uniformly, but not just two out of three end-points studied. Fahim et al (2003) have reported the antitumour activities of IA and Dimethylsulphoxide against solid Ehrlich carcinoma growth in mice. They have reported an increase in the life span and tumour growth inhibition ratio to 145.7 and 63.8% by IA respectively.…”
Section: Discussionmentioning
confidence: 99%